Accumulation and antigenicity of truncated porcine circovirus type 2 capsid protein in Escherichia coli cells - Titova, Anastasia D.; Kuleshova, Yuliya M.; Potapovich, Maxim I.; Prokulevich, Vladimir A. (Experimental Biology and Biotechnology, 2022)
This work examines accumulation of shortened version of porcine circovirus type 2 capsid protein (SOP protein) in the cells of bacterial strain Escherichia coli BL21-CodonPlus(DE3)-RIPL with plasmid pET-SOP, obtained in previous work. The gene for SOP protein was modified by deletion of the part (108 base pair) interfering expression in procaryotes, as well as optimisation of 93 rare codons. Under cultivation temperature 37 °C for 2 h after induction the proportion of target protein reaches of 24 % of the total cellular protein, which makes it possible to classify this strain as an effective industrial producer of target protein. During the cultivation of the producer at 37 °C, the target protein is in the cells in the native soluble form right after induction, but 1 h after the addition of the inducer, it is found mostly in insoluble multimeric form (inclusion bodies). When the cultivation temperature is lowered to 18–30 °C, the formation of inclusion bodies slows down, however the proportion of recombinant protein in the cells of the producer decreases to 15– 6 % respectively, which significantly reduces the profitability of the technological process. It has been established that the modified recombinant SOP protein obtained from bacterial cells of the producer strain retains its antigenic activity, which is confirmed by specific enzyme-linked immunosorbent assay analysis. These data allow us to consider studied protein as a promising candidate for a porcine circovirus type 2 vaccine.